The Letterbooks of Charles Robin-Collas & Company:: Changes and Challenges in Cape Breton Island’s Cod Fishery, 1886-1895 - Macleod, Erna (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2013)
Charles Robin-Collas and Company (CRC&C) was a fishing enterprise formed in 1886 that operated several fishing stations in Cape Breton and the Gaspé region, exporting fish to Europe, the Caribbean, New England, and South America in one of the largest global trade networks of the 19th century. The late 19th century marks a crucial transition in the company’s history characterized by technological innovation and the shift from a merchant-credit system to a cash economy. This article examines CRC&C letterbooks, which reveal the centrality of ecological circumstances and fishers’ agency in the company’s daily operations and in processes of social and economic change.